A Convenient and Atom‐Economic One‐Pot Selenium‐Chloride‐Mediated Synthesis of 2‐Arylselenopheno[2, 3‐b]indoles and Their Antifungal Activity. Issue 3 (19th February 2019) - Martins, Guilherme M.; do Carmo, Gabriele; Morel, Ademir F.; Kaufman, Teodoro S.; Silveira, Claudio C.
Abstract: A facile and convenient atom‐economic protocol for the one‐pot synthesis of 2‐aryl selenopheno[2, 3‐ b ]indoles, by an electrophilic cyclization of 3‐(arylalkynyl)indoles with SeCl2 prepared in situ as the selenium source, is reported. The tricyclic products were obtained in moderate to very good yields. The reaction was optimized, and its scope and limitations were systematically studied. It was observed that its performance was affected by the steric and electronic properties of the substituent attached to the nitrogen atom and to a lesser extent by the nature and position of the substituents of the pending aryl moiety. Halogen atoms located para to the alkynyl group caused an average of 20% yield reduction. The reaction was unsuccessful with substrates bearing an alkyl chain attached to one of the sides of the alkynyl moiety. The antifungal activity of selected tricyclic compounds was tested against a panel of clinically relevant yeasts, and one of the heterocycles was exceptionally effective against Cryptococcus neoformans and C. gatti . Abstract : A fun guy : The electrophilic cyclization of 3‐(arylalkynyl)indoles with SeCl2 provides access to 2‐aryl selenopheno[2, 3‐ b ]indoles in one pot. The scope and limitations of the reaction were assessed, and the antifungal activity of some tricyclic seleno‐derivatives was tested. One of the heterocycles was highly effective against Cryptococcus neoformans and C. gatti .